Contralateral recurrence of fallopian tube torsion: A case report - Daniil Khaitov, MD; Nagaraj Gabbur, MD (Elsevier, 2021)
Unilateral lower quadrant pain is a common presenting complaint in the emergency room with a wide differential. It is important to consider fallopian tube torsion in the differential, especially in premenopausal women, as fertility-sparing detorsion, especially in a woman with a previous salpingectomy or other fertility-affecting surgery, is essential. This case report is of a 25-year-old woman with worsening left lower quadrant abdominal pain over 24 h found to have an extraovarian cystic mass. When taking into consideration the patient with a history of contralateral fallopian tube torsion secondary to a paraovarian cyst, now presenting with left lower quadrant abdominal pain and a cystic extraovarian mass, immediate laparoscopic evaluation was warranted. Immediate intervention revealed an isolated fallopian tube torsion and resulted in surgical preservation of fertility.